PENGARUH PENGUASAAN VEKTOR TERHADAP HASIL BALAJAR FISIKA SISWA PADA MATERI HUKUM II NEWTON TENTANG GERAK KELAS X SMA NEGERI PADANG BOLAK JULU - Sari, Lia Purnama (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
The aim of this research was to know whether there was a significant influence between vector mastery on students’ achievementc in Newton’s law II about motion subject at tenth grade students of SMA Negeri 1 Padang Bolak Julu. The approach of this research was quantitave by applying descriptive and correlation method. The population of this research was all the tenth grade students of SMA Negeri 1 Padang Bolak Julu which include 10 classes or 210 students. By applying random sampling technique, based Taro Yamena formulate, the writer took the sample 68 students. In collecting the data, the writer used test. The writer used two ways to calculate the data. They are descriptive analysis and inferential analysis. Based on the data analysis, it could be gotten that the average of vector mastery was 69.22 and it was catagorized ”good”. While mean of students’ achievement in Newton’s law II was 66.73 and it was catagorized ”good. Based on statistics analysis calcution, it could be gotten that tcount = 16, in error level significant5%, confidence level significant 95%, df = N – 2 = 68 -2 = 66, it could be gotten that ttable= 1.67. It could be seen that tcount was greater ttable (16 >1.67). The hypothesis was accepted. It means that there was a significant influence between vector mastery on students’ achievement in Newton’ law II about motion subject at the tenth grade students of SMANegeri 1 Padang Bolak Julu.